Animation techniques - Roberts, Steve 1963- (The Crowood Press, 2021)
Animation can be used to illustrate, simplify and explain complicated subjects, as well as to transform stories into engaging, fantastical narratives. There are many types of animation, all of which can incorporate different artistic techniques such as sculpture, drawing, painting, printing and textiles. In this practical guide, animation tutor Steve Roberts explores the twelve basic principles of animation, demonstrating the different techniques available and offering helpful exercises for readers to practise in their chosen style. From pencils to pixels, flip books to feature films, and plasticine to puppets, this helpful book covers everything you need to know about how to start animating and will be of great interest for anyone looking to learn how to make their own animated films
"Everything you need to know about how to start animating" --Front cover
Keywords: Animation (Cinematography); Animated films; Animation (Cinéma); animations (visual works); animation (process); PERFORMING ARTS / Animation; Lehrbuch